Analysis of Internal Control System of Electronic Resident Id Card Production Service (KTP-EL) at Selimbau District Office - Rika Carolina; Umiaty Hamzani; Muhammad Fahmi; Syarif M. Helmi; Nina Febriana Dosinta (P3KM Politeknik Pertanian Negeri Samarinda, 2025)
This study aims to provide an overview and empirical evidence regarding the service system for issuing electronic identity cards (e-KTP), particularly within the institutions responsible for issuing them. The study focuses on internal control systems and the principles of public service delivery that influence the e-KTP issuance system. The type of research used is based on primary data, with the population comprising 28 employees of the Selimbau District Office. Secondary data were collected from books, theses, and journals related to the e-KTP issuance system. The methods used include organizational structure analysis, flowcharts, questionnaires, and compliance tests. The results of this study show that the implementation level of the government's internal control system reached 99.1%, and the implementation of public service principles reached 99.4%. Based on the questionnaire assessment criteria, the Selimbau District Office operates very effectively, with highly satisfactory internal control and public service standards. The effectiveness assessment based on the compliance test achieved a score of 100%, indicating a highly effective criterion. This means that employees have properly implemented the policies and procedures established for the e-KTP issuance process. However, there are still some obstacles, such as a complicated e-KTP issuance procedure, inadequate facilities and locations, inaccurate KTP collection times, frequent data/document inconsistencies, lack of specific guidance for the e-KTP issuance process, and the absence of a flowchart.